2010
DOI: 10.1016/j.medin.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Encuesta iberoamericana sobre delirium en pacientes críticos

Abstract: Although delirium is considered to be a common and preventable problem with serious implications for critically ill patients, the intensivist physicians surveyed do not use a tool for its evaluation in the ICU. Educational efforts are needed to disseminate the effectiveness and usefulness of the scales that allow for early and accurate diagnosis of delirium in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 91 publications
0
7
0
4
Order By: Relevance
“…(1-3) Surveys in Latin American, (4) Brazil (5) and Uruguay (6) revealed that most of the surveyed intensivists did not use a tool for delirium evaluation in their practices.…”
Section: Introductionmentioning
confidence: 99%
“…(1-3) Surveys in Latin American, (4) Brazil (5) and Uruguay (6) revealed that most of the surveyed intensivists did not use a tool for delirium evaluation in their practices.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of haloperidol being the most frequently prescribed drug are in line with previous surveys in ICU and non-ICU settings (Ely et al ., 2004; Fang et al ., 2008; Van Eijk et al ., 2008; Cadogan et al ., 2009; Davis and MacLullich, 2009; Patel et al ., 2009; Ceraso et al ., 2010; Forsgren and Eriksson, 2010; Mac Sweeney et al ., 2010; Devlin et al ., 2011). The type of antipsychotics reported in our survey also confirms the data reported by Meagher (2010) on delirium experts attending a workshop of the EDA, organized to explore the attitude toward delirium pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other surveys on delirium diagnosis and management have mainly been of healthcare providers working in an ICU (Ely et al ., 2004; Van Eijk et al ., 2008; Cadogan et al ., 2009; Patel et al ., 2009; Ceraso et al ., 2010; Forsgren and Eriksson, 2010; Mac Sweeney et al ., 2010), focusing on tools to assess for delirium, sedation practice, and the pharmacological management of delirium. Haloperidol was reported as the most commonly used drug to treat delirium, and the CAM-ICU was the most frequently used tool to assess for delirium, followed by the Intensive Care Delirium Screening Checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current study is particularly noteworthy because it provides preliminary evidence regarding delirium awareness in two groups of health care providers, which have never been considered as a target for education in previous studies. Indeed, previous surveys to evaluate delirium knowledge have been conducted in various settings of care, among doctors (Ely et al 2004;Fang et al 2008;Van Eijk et al 2008;Cadogan et al 2009;Davis and MacLullich 2009;Patel et al 2009;Ceraso et al 2010;Forsgren and Eriksson 2010;Mac Sweeney et al 2010;Devlin et al 2011;Morandi et al 2013), nurses (McCrow et al 2013, pharmacists (Devlin et al 2011), nurses and doctors (Van Eijk et al 2008), or among an audience of doctors, nurses, pharmacists, physician assistants, and respiratory care practitioners (Ely et al 2004;Patel et al 2009), but none of these surveys have specifically targeted psychologists and physiotherapists.…”
Section: Discussionmentioning
confidence: 99%